Kemitraan Pemerintah dan Masyarakat Lokal dalam Pengelolaan Hutan Mangrove di Pantai Utara Kota Surabaya - Jose Maria Da Conceicao Freitas (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purpose of this study was to determine and describe the partnership between of Surabaya government with local communities on mangrove forestsmanagement in the North Coast Surabaya. This research is conducted by qualitative descriptive method. Based on the research results, it is known that the partnership between the government of Surabaya with the local community (comanagement approach) provide positive value on the mangrove forests management. People who benefit from the mangrove forest participate in determining management decisions that affect their well-being, while the government got benefits from reduced liability manage. In addition, comanagement approach could increase the sense of belonging in the community, so there was a will of its own to preserve mangrove. But in this case, several steps that needs to be done by local government, among others: local government divided each authority were clearly based on formal rules; local government empower local communities associated with mangrove forest management, as well as set up an authorized institution in the management of resources such as beach protection as partners with Surabaya government on collaboration who could represent their respective interests (mangrove forest management) and recognized by the community.